DNA sequence variation in normal pigmentation - John, Premila Rozanne (My University, 2014)
Pigmentation is one of the most visible physical characteristics in humans and can be influenced by various factors, both environmental and genetic. The genes in this polygenic trait take part in the stimulation o f and production of melanin. This study aimed to explore the role o f the MC1R, TYR and TYRP1 genes in normal pigment variation. Variation in the MC1R gene was investigated in the Negroid and San populations, and a group o f red-haired Caucasoid individuals. The two African groups had fewer non-synonymous than synonymous mutations. The F196L (7/59 chromosomes) and T314T (25/59) variants were significantly more common in the Negroids than the San (p<0.05 and pO .O l), who were relatively less diverse at the MC1R locus. The L50L variant (3/34) was significantly more common in the San (p<0.05). The Negroids and San did not share any alleles with the red-haired Caucasoids, who were all found to be either homozygous for one mutation or heterozygous for two different mutations. They revealed four novel mutations S83P, Y152X, A171N and P256P at low frequencies (1/14). A random group of normally pigmented Negroid and Caucasoid individuals were investigated for sequence variation at the TYR and TYRP1 loci. In the TYR gene S192Y (p<0.05) and R402Q (p=0.01) mutations, observed in 8/30 and 6/28 chromosomes, were significantly associated with the Caucasoids, while the Negroids did not vary at this locus. TYR, therefore, probably plays a significant role in pigmentation differences between Caucasoids and Negroids. The TYRP1 gene in both populations, however, was found to lack significant variation. In conclusion, this study indicates that variation at the MC1R and TYR loci may play a .significant role in normal pigment variation in humans, but that the TYRP1 gene appears to play a less significant role.
Thesis (M.Sc. (Human Genetics))--University of the Witwatersrand, Faculty of Medicine, 1999.